Evaluation of (anti)genotoxic activities of Phyllanthus niruri L. in rat bone marrow using the micronucleus test - Fernando Márlisson de Queiroz; Kayo Wanderson de Oliveira Matias; Mylena Mylana Freire da Cunha; Aline Schwarz (Universidade de São Paulo, 2013)
Phyllanthus niruri L. (Euphorbiaceae), known as "quebra-pedra" (Portuguese for "stonebreaker"), is an herb used for kidney disorders. In light of its frequent use by the population, the present study aimed to investigate the genotoxic, antigenotoxic and cytotoxic activities of a standardized P. niruri extract in bone marrow rats. Three groups of 12 animals were treated daily by gavage over a period of 30 days, with 50, 150 or 250 mg/kg of P. niruri extract aqueous solution. The control group (n = 12) received tap water. At the end of treatment (day 31), groups were divided into two minor subgroups (n=6/group) and received cyclophosphamide (50 mg/kg, i.p.) or saline 0.9% (i.p.). After 24 hours, we evaluated the frequency of micronucleated polychromatic erythrocytes for each animal (MNPCE) at 1000 PCE. Cytotoxicity was evaluated with the PCE/NCE ratio (NEC = normochromatic erythrocytes). General toxicity was assessed during treatment using the parameters of body weight gain, ration and water consumption. The dry extract did not provoke changes in body weight, weight gain, ration and water intake or changes in the frequency of MNPCE or cytotoxicity in bone marrow. We propose that the P. niruri extract used here showed no genotoxic, antigenotoxic and cytotoxic activities under the experimental conditions. Phyllanthus niruri L. (Euphorbiaceae), conhecida como "quebra-pedra", é uma planta medicinal utilizada frequentemente pela população no tratamento de problemas renais. Foram avaliadas as atividades genotóxicas, antigenotóxicas e citotóxicas de um extrato padronizado dessa espécie em ratos. Três grupos de doze animais foram tratados durante trinta dias, por gavagem, com 50, 150 ou 250 mg/kg/dia de solução aquosa do extrato de P. niruri e um grupo controle (n=12) recebeu água destilada pela mesma via. No final do tratamento os grupos foram divididos em dois subgrupos (6 animais/grupo) e receberam uma dose única de ciclofosfamida (50 mg/kg, i.p.) ou de solução salina 0,9% (i.p.). Após 24 horas, a frequência de eritrócitos policromáticos micronucleados (EPCMN) foi avaliada em 1000 EPC. A citotoxicidade foi avaliada pela relação entre eritrócitos policromáticos e normocromáticos (EPC/ENC) e a toxicidade geral foi avaliada através dos parâmetros de ganho de peso corporal, consumo de ração e ingestão hídrica. O extrato seco não provocou alterações significativas no peso corporal, ganho de peso e consumo de ração em relação ao grupo controle, nem alterações na frequência de EPCMN ou citotoxicidade em medula óssea. Dessa maneira, pode-se concluir que P. niruri não apresentou atividades genotóxica, antigenotóxica e/ou citotóxica nas condições experimentais executadas.